Swedish School of Library and Information Science 50 years! A multi-colour bibliometric portrait - Gustaf Nelhans; Björn Hammarfelt (Information Research: An International Electronic Journal)
Introduction. The aim of the article is to convey an overall picture of the research conducted at Swedish School of Library and Information Science (SSLIS).